2006
DOI: 10.1088/0264-9381/23/22/021
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dilaton gravity in two dimensions with fermionic matter

Abstract: Path integral quantization of generic two-dimensional dilaton gravity nonminimally coupled to a Dirac fermion is performed. After integrating out geometry exactly, perturbation theory is employed in the matter sector to derive the lowest order gravitational vertices. Consistency with the case of scalar matter is found and issues of relevance for bosonisation are pointed out.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 78 publications
4
82
0
Order By: Relevance
“…Though those simplified models do not capture the detailed physics of black hole those models contain the information loss paradox in a significant way [8,10,11]. Scattering of fermion was not studied only in connection with information loss, scattering of boson was also studied in [12,13,14] in the same context. The scattering of chiral fermion off dilaton black hole was not ignored too.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Though those simplified models do not capture the detailed physics of black hole those models contain the information loss paradox in a significant way [8,10,11]. Scattering of fermion was not studied only in connection with information loss, scattering of boson was also studied in [12,13,14] in the same context. The scattering of chiral fermion off dilaton black hole was not ignored too.…”
mentioning
confidence: 99%
“…The scattering of Dirac fermion itself is an interesting problem [6,7,8,9,12,13,14]. If Dirac fermions are replaced by the chiral fermion it makes the analysis more complex because the chiral fermions generate anomaly in the energy momentum sector when they couple to gravity [15].…”
mentioning
confidence: 99%
“…If the matter extension yields additional second class constraints, as e.g. in the case of fermions, 48 the Poisson bracket should be replaced by a the Dirac bracket. The three constraints G I form a closed nonlinear algebra 20) with structure functions f K IJ .…”
Section: Exact Path Integral Quantizationmentioning
confidence: 99%
“…Nonetheless, it should be remembered that conformal invariance applies to the complete Lagrangian, here (1.69), including the (asymptotic) matter states. 48 q In these works a stretched horizon was imposed as a boundary, implemented by suitable boundary constraints. It was then found that these constraints break parts of the symmetry, which allowed to deduce the correct entropy by means of the Cardy formula.…”
Section: Two-dimensional Dilaton Gravity With Boundariesmentioning
confidence: 99%
“…1, we work out the extensions of all dilaton models featuring in the up-to-date table of Ref. [20]. The fifth column shows the identifications that must be performed in order to relate the extended theories to their unextended counterparts, for the reference case in which η 0 3 = 1.…”
Section: Extended Modelmentioning
confidence: 99%